PERAN MUROQOBAH JUZ 30 SEBELUM BELAJAR MENGAJAR DALAM PENINGKATAN PERILAKU SISWA KELAS VII SMP YAYASAN PENDIDIKAN MA’ARIF MOJOWARNO JOMBANG - Kurnia Aji, Rifki; Inayatul Ilahiyah, Iva (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
his study aims to examine the role of Muroqobah Juz 30 before the teaching and learning process in improving the daily behavior of seventh-grade students at the Ma’arif Education Foundation Junior High School in Mojowarno, Jombang. This study employs a qualitative approach using a case study design to provide an in-depth and detailed description of the role of Muroqobah Juz 30 prior to the learning process. Data were collected through observation, interviews, and documentation involving the principal, teachers, mentors, students, and parents. The data were analyzed through simplification, presentation, and drawing of conclusions, and their validity was tested using source and method triangulation. The findings of this study indicate that Muroqobah Juz 30 prior to the learning process at SMP Yayasan Pendidikan Ma’arif Mojowarno Jombang serves to accustom students to reading the Qur’an, maintain their memorization, and instill discipline and readiness for learning. The Muroqobah Juz 30 activity at SMP Yayasan Pendidikan Ma’arif Mojowarno Jombang has a positive impact on fostering discipline, ethics, responsibility, and learning readiness among seventh-grade students, thereby contributing to the development of students’ moral character and personality. The Muroqobah Juz 30 activity before class at SMP Yayasan Pendidikan Ma’arif Mojowarno Jombang serves to improve discipline, readiness to learn, and the daily behavior of seventh-grade students at SMP Yayasan Pendidikan Ma’arif Mojowarno.